Dynamics in quality assurance and evaluation in higher education : a case study of Chile - Vega, Ariel (fi=Turun yliopisto|en=University of Turku|, 2018)
Improvement by means of quality seems to be a common belief shared by education policy makers worldwide. Quality Assurance and Evaluation (QAE) is one clear example of standardization of policy making. Policy standardization offers an oversimplified view of education. It reduces education into prescribed standards or best practices when reality is far more complex. Therefore, it is important to analyze policy in its context, including the relations among actors and their socio-historical complexities. To account for those complexities, Comparative Analytics of Dynamics in Education Politics (CADEP) is a theoretical approach to policy analysis focused on the characteristics of interactions (dynamics) between relevant actors in education politics and their context, rather than on policy results. This study investigates the dynamics in QAE in Chilean higher education. It is based on the analysis of key documents, and interviews to four key actors identified as relevant in the case of quality assurance. Based on the analysis of both sets of data, it is possible to understand the political situation and political possibilities and their interplay allows us to identify four dynamics. These four dynamics provide valuable insights into some specific aspects of the Chilean quality assurance system. Due to the lack of interviews to more key actors, its conclusions cannot be generalized to the entire system. Nevertheless, they provide a broader understanding of the Chilean context and its complexities, and its design could be replicated with a bigger sample of relevant actors.